Sequential Endoscopic Findings of a Tuberculous Esophageal Ulcer that Developed into a Traction Diverticulum - Serin Cha; Dong Han Yeom (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2020)
Esophageal diverticula are uncommon lesions that are usually classified according to location, layers of the wall, and underlying pathogenesis. A true traction esophageal diverticulum, which is commonly seen in the middle one-third of the thoracic esophagus, occurs secondary to mediastinal inflammatory lesions, such as those caused by tuberculosis. Esophageal tuberculosis usually develops secondary to tuberculous lymphadenitis or lung lesion; it manifests with various endoscopic findings such as single or multiple ulcers, elevated lesions with ulcers at the center, extrinsic compressions, fistulas, and rarely, anthracosis. Its shape can vary greatly depending on disease progression and treatment. Herein, we report sequential endoscopic findings of a tuberculous esophageal ulcer that turned into a depressed lesion with black-pigmentation, finally developing into a typical traction esophageal diverticulum in a patient with mediastinal lymphadenitis.